KARAKTERISTIK MEDIA PEMBELAJARN INTERAKTIF UNTUK SISWASEKOLAH MENENGAH PERTAMA - Amarullah, Taufik Abdul Hasan; Wiwita, Risma (Jurnal Manajemen Pendidikan, 2024)
Learning media and secondary school students and Junior High School students are interrelated, and the link between the two is the learning process itself. itself. The purpose of this research is to identify the characteristics of characteristics of interactive learning media suitable for junior high school students. The method used in this research is a literature study, which involves analyzing books, articles and other references. The method used in this research is a literature study, which involves analyzing books, articles, and other references. These media come in a variety of formats, including interactive simulations, learning movies, digital platforms, and instructional games. instructional games. Through educational films and interactive simulations, junior high school students can experience various scenarios in a safe environment. In addition, learning through instructional games can attract junior high school students. This digital learning platform can be used independently by schools. Therefore, it can be concluded that the existence of interactive learning media greatly influences the teaching and learning process. Therefore, it can be concluded that the existence of interactive learning media greatly affects the teaching and learning process. Moreover Moreover, in the modern era that is filled with technology, interactive media is very suitable for learning activities. The results of this research in the form of a description of interactive learning media, and its implementation can be used as a reference to choose the right media in this digital era. to choose the right media in today's digital era.